Design of a process mining methodology for the development of business and scientific-academic projects - Morales Ramírez, Alejandra (2024)
Process mining enables organizations to discover, analyze, and enhance their business processes by extracting knowledge from event logs available in current information systems. This research proposes a process mining methodology for developing business and scientific-academic projects, consisting of nine phases: planning and scope, data preprocessing, data processing, flow control analysis, performance analysis, role analysis, results presentation, results publication, and transfer and monitoring. This methodology results from the researcher’s literature review, analysis of published methodologies, and their knowledge and experiences. Future research will apply this process mining methodology to various case studies in business and scientific-academic domains. This research aims to analyze the methodology’s efficiency, its application’s ease and relevance, and the congruence between its phases.